Analysis of the interactions in FCCF:(H2O) and FCCF:(H2O)2 complexes through the study of their indirect spin–spin coupling constants - Caputo, Maria Cristina (2017)
A theoretical study of FCCF:(H2O)n complexes, with n = 1 and 2, has been carried out by means of ab initio computational methods. Three kinds of interactions are observed in the complexes: H···π and H···F hydrogen bonds and O···FC tetrel bonds. The indirect spin–spin coupling constants have been calculated at the CCSD/aug-cc-pVTZ-J computational level. Special attention has been paid to the dependence of the different intramolecular coupling constants in FCCF on the distance between the coupled nuclei and the presence or absence of water molecules. The exceptional sensitivity shown by these coupling constants to the presence of water molecules is quite notorious and can provide information on the bonding structure of the molecule.